2012
DOI: 10.1172/jci45850
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel pneumococcal vaccine antigen preferentially expressed during meningitis in mice

Abstract: Streptococcus pneumoniae is the most common cause of severe bacterial meningitis in children, the elderly, and immunocompromised individuals. To identify virulence factors preferentially expressed during meningitis, we conducted niche-specific genome-wide in vivo transcriptomic analysis after intranasal infection of mice with serotype 4 or 6A pneumococci. The expression of 34 bacterial genes was substantially altered in brain tissue of mice infected with either of the 2 strains. Ten upregulated genes were comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 66 publications
3
48
0
Order By: Relevance
“…Some of the changes in expression of metabolic genes may be associated with an upregulation of the catabolite control protein A (ccpA) gene, which has been shown to induce glycolysis as well as expression of the ATP-binding protein MsmK (55), which regulates the 2-oxoacid dehydrogenase complex, lactate oxidase, and malA. The IAV-dispersed cells also upregulated glpO (␣-glycerophosphate oxidase), which was recently shown to act as a virulence factor during meningitis (56). Genes encoding neuraminidases A and B (nanA and nanB), enzymes involved in production of UDP-sugars and glycerolipid metabolism, were among the most highly upregulated genes observed (428-and 924-fold, respectively).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the changes in expression of metabolic genes may be associated with an upregulation of the catabolite control protein A (ccpA) gene, which has been shown to induce glycolysis as well as expression of the ATP-binding protein MsmK (55), which regulates the 2-oxoacid dehydrogenase complex, lactate oxidase, and malA. The IAV-dispersed cells also upregulated glpO (␣-glycerophosphate oxidase), which was recently shown to act as a virulence factor during meningitis (56). Genes encoding neuraminidases A and B (nanA and nanB), enzymes involved in production of UDP-sugars and glycerolipid metabolism, were among the most highly upregulated genes observed (428-and 924-fold, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…As an example, glpO was upregulated 60-fold and 509-fold in IAV-dispersed cells compared to biofilm and 37°C planktonic cells, respectively. glpO encodes a surface-expressed ␣-glycerophosphate oxidase involved in glycerol metabolism and was recently identified as a promising vaccine antigen in a screen for S. pneumoniae genes expressed during meningitis (56). Glycerol is more abundant than glucose in the brain, whereas glucose is more abundant in the blood (70,71).…”
Section: Discussionmentioning
confidence: 99%
“…pneumoniae is a diverse and adaptable pathogen, capable of surviving in a range of niches within its human host. Previous studies from our laboratory have identified changes in in vivo transcriptional profile within a given strain that facilitate survival in distinct host niches (nasopharynx, lungs, blood, and brain) and/or aid progression from one niche to another (26,27,35,36). However, genetic differences between strains also result in pneumococci with inherent tropism for one niche over another.…”
Section: Discussionmentioning
confidence: 99%
“…1C). Specifically, vaccine candidates (i.e., antigens) were discovered by building on the fundamental insight that S. pneumoniae colonizes the nasopharynx as a biofilm and that disease progression occurs when external triggers resulting from changes in the nasopharyngeal environment prompt escape from the asymptomatic biofilm of bacteria with a changed transcriptional profile associated with increased virulence (22,23,34). Although current vaccines have provided protection and expanded coverage over time (Fig.…”
Section: Significancementioning
confidence: 99%